The Effect of Environmental Disclosure and Performance on Profitability in the Companies Listed on the Stock Exchange of Thailand (SET) - Indah Fajarini Sri Wahyuningrum; Muhammad Ihlashul Amal; Suci Sularsih (Jurnal Ilmu Lingkungan, 2021)
The main objective of this study is to determine the empirical evidence of the effect of environmental disclosure, environmental performance, company age, and company size on profitability. The purposive sampling method was used to determine the sample of companies and obtained 85 companies from a total population of 100 large companies listed on the Thailand Stock Exchange (SET) in 2018. The data analysis technique used was multiple linear regression analysis using analysis tool IBM SPSS Statistics version 26. The results of this study prove that environmental disclosure has a significant positive effect on profitability. Environmental performance and company size have a significant negative effect on profitability. On the other hand, company age is not proven to have a significant effect on profitability. Based on the research results, it can be concluded that more extensive environmental disclosure is able to increase the achievement of profitability. However, company age is not a factor affecting profitability. Meanwhile, company size and environmental performance as measured by total assets and the existence of ISO 14001 certifications are proven to reduce the level of company profitability. This study also has several limitations, including the time period which is limited to only one time period, namely 2018. It is expected that further studies can expand the time period by more than one year. This is since using a time period of more than one year can illustrate the effect of environmental disclosure and environmental performance, company age and company size on the profitability achieved by the companies.  In addition, it is expected that the results of this study can provide input to companies to be more concerned regarding company performance activities, especially on the environment because there are still many companies that have low levels of environmental disclosure even though environmental disclosure in Thailand is still voluntary.